The “True Man” and His Gun: On the Masculine Mystique of Second Amendment Jurisprudence - Christensen, C. D. (2017)
The Supreme Court’s recent Second Amendment jurisprudence raises serious normative questions for the use of self-defense with a firearm. This jurisprudence also implicates our prevailing social norms with respect to socially constructed and structurally pervasive gender roles. I argue that a peculiarly American conception of masculinity underpins the judicial construction of the Second Amendment’s core purpose as guaranteeing the right to armed defense of one’s self and one’s home. The Court’s recent Second Amendment rulings create an individual protection for gun ownership and incorporate the same against the States. But the Court’s reasoning entangles this protection with an implicit valuation of manhood that reifies the notion that “true men” do not retreat in the face of danger. In so entangling, the Court establishes a right to gun ownership that is politically free but legally male. This Article explores the socio-legal structures that underpin the Court’s reasoning to explain (a) how the right to keep and bear arms arises from a dubious ideal of the American “man,” and thus how (b) the purposes for which one may keep and bear arms galvanizes a particular masculine type within our Second Amendment jurisprudence. That type establishes a problematic cultural narrative of and ethos for manhood in America; consequently, this jurisprudence establishes a dominant masculinity predicated upon firearm ownership. That masculinity complicates, and may even impede, the social evolution of subordinated masculinities and shifts the social hierarchy of masculinities to empower and privilege gun-owning males